OsNAC129 Regulates Seed Development and Plant Growth and Participates in the Brassinosteroid Signaling Pathway - Jin, Su-Kui; Zhang, Ming-Qiu; Leng, Yu-Jia; Xu, Li-Na; Jia, Shu-Wen; Wang, Shui-Lian; Song, Tao; Wang, Ruo-An; Yang, Qing-Qing; Tao, Tao; Cai, Xiu-Ling; Gao, Ji-Ping (Frontiers in Plant Science, 2022)
Grain size and the endosperm starch content determine grain yield and quality in rice. Although these yield components have been intensively studied, their regulatory mechanisms are still largely unknown. In this study we show that loss-of-function of OsNAC129, a member of the NAC transcription factor gene family that has its highest expression in the immature seed, greatly increased grain length, grain weight, apparent amylose content, and plant height. Overexpression of OsNAC129 had the opposite effect, significantly decreasing grain width, grain weight, apparent amylose content, and plant height. Cytological observation of the outer epidermal cells of the lemma using a scanning electron microscope revealed that increased grain length in the osnac129 mutant was due to increased cell length compared with wild-type (WT) plants. The expression of OsPGL1 and OsPGL2, two positive grain-size regulators that control cell elongation, was consistently up-regulated in osnac129 mutant plants but down-regulated in OsNAC129 overexpression plants. Furthermore, we also found that several starch synthase-encoding genes, including OsGBSSI, were up-regulated in the osnac129 mutant and down-regulated in the overexpression plants compared with WT plants, implying a negative regulatory role for OsNAC129 both in grain size and starch biosynthesis. Additionally, we found that the expression of OsNAC129 was induced exclusively by ABA in seedlings, but OsNAC129-overexpressing plants displayed reduced sensitivity to exogenous brassinolide. Therefore, the results of our study demonstrate that OsNAC129 negatively regulates seed development and plant growth, and further suggest that OsNAC129 participates in the BR signaling pathway.